A finite element study of the effect of vertical loading on the in-plane behavior of concrete masonry infills bounded by steel frames. (15th June 2016) - Chen, Xi; Liu, Yi
Highlights: A finite element (FE) study for in-plane behaviour of masonry infilled steel frames. Six infilled frame specimens under combined vertical and lateral loads were tested. Effect of vertical loading on the stiffness and strength of the infill was studied. An analytical method was proposed to account for the effect of vertical loading. The proposed method compares well with FE results on a wide range of parameters. Abstract: A finite element study was performed to investigate the effect of vertical loading on the in-plane lateral behavior and strength of concrete masonry infills bounded by steel frames. An experimental program was also conducted and results were used to verify the finite element model. Parameters considered in the finite element study included the vertical load level and application method, infill aspect ratio, infill compressive strength, and bounding frame stiffness. Results showed that when applied as a uniformly distributed load on the frame beam, an optimal load level was identified and the vertical load, when applied within this load level, was found to be beneficial to the lateral stiffness and strength of the infilled frame. When applied as point loads on columns, the vertical load was shown to reduce the lateral strength of the infilled frame. Based on the regression analysis on finite element results, a simplified analytical model was proposed to account for the effect of vertical loading through the use of a modification factor on the lateral stiffness and strength of infilled steel frames. The proposed model was shown to provide results in good agreement with finite element values over a wide range of load levels, infill material strengths, and frame stiffnesses.